2017
DOI: 10.3847/1538-3881/aa9894
|View full text |Cite
|
Sign up to set email alerts
|

The Pan-Pacific Planet Search. VII. The Most Eccentric Planet Orbiting a Giant Star

Abstract: Radial velocity observations from three instruments reveal the presence of a 4 M Jup planet candidate orbiting the K giant HD 76920. HD 76920b has an orbital eccentricity of 0.856±0.009, making it the most eccentric planet known to orbit an evolved star. There is no indication that HD 76920 has an unseen binary companion, suggesting a scattering event rather than Kozai oscillations as a probable culprit for the observed eccentricity. The candidate planet currently approaches to about four stellar radii from it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
6

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 120 publications
(130 reference statements)
4
59
6
Order By: Relevance
“…The ASAS V band photometry has a mean value of 7.493±0.014 mag. We note that the orbit of HD 7449b has a gap in phase coverage near the RV peak, and that its shape is quite similar to that of the recentlydiscovered highly eccentric planet HD 76920b (Wittenmyer et al 2017b). In that work, as in this one, the authors noted that the system's best-fit e and ω could not be reproduced by the double-circular degeneracy (e.g.…”
Section: Hd 7449mentioning
confidence: 62%
“…The ASAS V band photometry has a mean value of 7.493±0.014 mag. We note that the orbit of HD 7449b has a gap in phase coverage near the RV peak, and that its shape is quite similar to that of the recentlydiscovered highly eccentric planet HD 76920b (Wittenmyer et al 2017b). In that work, as in this one, the authors noted that the system's best-fit e and ω could not be reproduced by the double-circular degeneracy (e.g.…”
Section: Hd 7449mentioning
confidence: 62%
“…Butler et al 1997;Hellier et al 2011;Wright et al 2012), as well as planets moving on orbits so eccentric that they more closely resemble the orbits of comets than the planets in our own backyard (e.g. Wittenmyer et al 2007;Tamuz et al 2008;Wittenmyer et al 2017b). We also found many systems with multiple planets moving on orbits locked in mutual meanmotion resonance (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Wolszczan, & Frail 1992;Mayor & Queloz 1995;Wright et al 2012), to the highly eccentric worlds found by radial velocity surveys (e.g. Jones et al 2006;Tamuz et al 2008;Wittenmyer et al 2017c), as more planets have been that truly resemble our own (e.g. Marcy et al 2002;Wittenmyer et al 2014bWittenmyer et al , 2017aAgnew et al 2018;Buchhave et al 2018).…”
Section: Introductionmentioning
confidence: 98%